Iron oxide nanoparticles for diagnosing and treating degenerative orthopaedic diseases: a review - XL Zhu; QC Fu; LF Jiang; LM Zheng (European Cells & Materials)
The prevalence of degenerative orthopaedic diseases, such as osteoarthritis, osteoporosis, and intervertebral disc disease, has increased due to the increasing prevalence and unsatisfactory therapeutic methods. Recently, different types of bioactive nanomaterials, such as iron oxide nanoparticles (IONPs), have raised much concern due to their ability to positively regulate the bone remodelling balance. Due to their magnetic characteristics, IONPs have been applied in magnetic resonance imaging in the clinic, but their ability to treat degenerative orthopaedic diseases has recently been shown both in vitro and in vivo. However, a comprehensive review of the potential utilization of IONPs in the orthopaedic field is lacking. Here, we summarize previous works in this review and discuss future research directions in this field.